2016
DOI: 10.1111/jcpt.12450
|View full text |Cite
|
Sign up to set email alerts
|

Long-term immune and virological response in HIV-infected patients receiving antiretroviral therapy

Abstract: Results of this study show that a large proportion (73%) of patients have rapid and successful immune and virological responses to ART and that factors which predict this response include starting ART early, whereas viral load is low and CD4 count is high, with fewer drugs. These results further support the ongoing need for ongoing programmes to increase early HIV testing, early linkage to and treatment with ART, and increased viral suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…These effects could be explained because CD4 count at treatment initiation is a biological predictor of a better immunological function and slower disease progression. 32 35 However, our stratified analysis indicated that CD4 levels increase the odds of VF after 2013, but the association is marginal (OR of 1.08; 95% CI of 1.01–1.15). Although the association of CD4 levels and VF after 2014 is counterintuitive, it could be explained by a few reasons.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These effects could be explained because CD4 count at treatment initiation is a biological predictor of a better immunological function and slower disease progression. 32 35 However, our stratified analysis indicated that CD4 levels increase the odds of VF after 2013, but the association is marginal (OR of 1.08; 95% CI of 1.01–1.15). Although the association of CD4 levels and VF after 2014 is counterintuitive, it could be explained by a few reasons.…”
Section: Discussionmentioning
confidence: 66%
“…For example, it has been shown that individuals with a lower perception of risk have a poorer adherence 36 which could be the case for those PLWH with higher CD4 count (fewer symptoms and warning signs for disease progression) 36 , 37 Besides the direct association of poor adherence and VF, intermittent ART adherence has also been associated with CD4 variability, which is also associated with VF. 37 In contrast, lower VL levels at treatment initiation are associated with better prognosis and successful viral responses 32 This could be explained because VL is a predictor for disease progress. Patients with higher levels at treatment initiation presented a more complex and advanced disease than patients with lower levels.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Women with severe immunosuppression and CD4+ T lymphocyte counts below 200 cells/mm 3 have an even greater risk of developing cervical intraepithelial neoplasia [14][15][16][17][18] where immunosuppression is a predictor of the development of cervical lesion in women with HIV/AIDS, however, the use of antiretroviral therapy may strengthen the immune response and may be a protective factor for these women. 19,20 Considering HPV as the main risk factor for the development of CC, studies point to the strong association of harmful habits such as smoking, alcohol use and other drugs with high-risk of HPV infection. 15,21 Women living with HIV and using tobacco have a prevalence of cervical intraepithelial neoplasia four times higher than non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Current HIV treatment based on ART arrests the replication cycle of HIV and has been shown to increase immune cell numbers in most PLWH. 33-35 However, some PLWH are “immunological nonresponders” who do respond to ART with cessation of viral replication, but fail to exhibit restoration of CD4 + cell counts. 36-38 More commonly yet, PLWH who receive regular ART treatment that halts viral replication typically show varying levels of persistent non-resolving inflammation.…”
Section: Hiv Effects and Antiretroviral Therapymentioning
confidence: 99%